Development of new two dimensional FCC-MDW code with wavelength/time scheme in optical code division multiple access (OCDMA) network systems - Nui Din Keraf author (School of Computer and Communication Engineering, 2017)
The scope of this study involves with the capability of 2-D code by using W/T methods to suppress the influence of the MAI effect in the incoherent SAC-OCDMA system. A number of studies have examined the relationship between the MAI effect and the degradation of system bit error rate (BER) (Shiraz & Karbassian, 2012; Yin & Richardson, 2007). This newly proposed 2-D signature code can be obtained by combining of 1-D MDW (Aljunid et. al., 2004) and 1-D FCC (Rashidi, Aljunid, Ghani, Fadhil, Anuar, & Arief, 2014) codes known as 2-D FCC-MDW. The scheme used is based on wavelength and time encoding decoding process. Each user will be assigned a hybrid signature code where the optical pulses will be first encoded in the wavelength domain using MDW code scheme and later the FCC code will be encoded in the time domain. The serious issues to deal with when designing the code in OCDMA system with satisfactory performance is that the correlation properties and the number of users can be supported (Chen, 2007). Hence, to demonstrate the potential of this approach and its suitability for the application, the mathematical derivation is investigated. A simulation which uses OPTISYS simulation software Version 7.0 used to simulate the data which practically replicate a real system. The comparison will be carried out between the theoretical (mathematical analysis) and simulation data. In order to verify the analytical methods, all the mathematical development based on 2-D FCC-MDW code will be compared with the existing similar structured 2-D codes.